Couples' affect dynamics: Associations with trait hostility and physical intimate partner violence. (December 2019) - Tiberio, Stacey S.; Capaldi, Deborah M.
Abstract: Whether men's and women's reciprocation of their intimate partners' negative and positive affect during conflictual topic discussions accounted for the association between their trait hostility and perpetration of physical intimate partner violence (IPV) was examined within a dyadic model, using concurrent measurement. The work builds on that of Dr. Tom Dishion regarding hostile and coercive interactions in key relationships on risk outcomes and the importance of moment-by-moment influences in social interactions. Using dynamic development systems theory and a community sample of at-risk men ( N = 156) and their female partners, the hypothesis that quicker negative and slower positive affect reactivity would account for physical IPV perpetration beyond trait hostility was tested. Results suggest that, for women, quicker negative affect reactivity partially explains the hostility IPV association, whereas for men, trait hostility of both partners best explained their perpetration of physical IPV. No support was found for positive affect reactivity as a protective relationship process for IPV involvement. Findings are in line with other studies indicating men were less likely to engage in negative reciprocity relative to women. Furthermore, findings highlight how both partners' individual characteristics, communication patterns, and emotion regulation processes germane to the romantic relationship impact the likelihood of experiencing physical IPV.